2013
DOI: 10.1080/09712119.2012.738212
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding ofMorinda citrifoliafruit juice on the biophysical parameters of healthy as well as mastitis-affected cow milk

Abstract: The present study was conducted to assess the effect of Morinda citrifolia fruit juice on milk characteristics of healthy as well as mastitis-affected dairy cow. A total of 25 adult dairy cows were selected out of which 13 were healthy and 12 were found affected with sub-clinical mastitis. M. citrifolia fruit juice was fed to dairy cow at the rate of 100 ml/day/animal orally. The average pH of the normal milk and mastitis-affected milk was 6.6090.12 and 7.290.17, respectively. The feeding of M. citrifolia juic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…In the mastitis milk, level of electrical conductivity increases due to changes in ionic concentration which resulted in the decrease in the level of lactose and K+ and increase in the level of Na+ and Cl (Kitchen, 1981;Kaşikçi et al, 2012). Sunder et al (2013a) found that feeding of M. citrifolia decreased the electrical conductivity from 5.5 mho to less than 5.0 mho, which resulted in decrease in the milk pH (7.0 to 6.6) thus reducing the total microbial load in the milk. Level of microbial load was also decreased from 5.13 x 108 to 3.54 x108.…”
Section: Antimastitis Properties In Cattlementioning
confidence: 99%
See 2 more Smart Citations
“…In the mastitis milk, level of electrical conductivity increases due to changes in ionic concentration which resulted in the decrease in the level of lactose and K+ and increase in the level of Na+ and Cl (Kitchen, 1981;Kaşikçi et al, 2012). Sunder et al (2013a) found that feeding of M. citrifolia decreased the electrical conductivity from 5.5 mho to less than 5.0 mho, which resulted in decrease in the milk pH (7.0 to 6.6) thus reducing the total microbial load in the milk. Level of microbial load was also decreased from 5.13 x 108 to 3.54 x108.…”
Section: Antimastitis Properties In Cattlementioning
confidence: 99%
“…Capsicum annuum, Lepidium sativum, Allium sativum, Sesamum indicum, Citrus limon, Zingiber officinale, Citrullus colocynthis, Curcuma longa, Amomum subulatum, Sesamum indicum, Cuminum cyminum, Rosa indica, Centratherum anthelmisticum, Triticum aestivum, Nigella sativa and Peganum harmala (Dilshad et al, 2009). In many of the reports, the antibacterial activity of the plant extracts were described against the organisms responsible for mastitis, however, Sunder et al (2013a) reported the treatment of mastitis by feeding of M. citrifolia in dairy cows. Sunder et al (2013a) observed that oral feeding of noni fruit juice (100 ml) to dairy cows is effective for treatment of mastitis.…”
Section: Antimastitis Properties In Cattlementioning
confidence: 99%
See 1 more Smart Citation
“…[66] 50 g/kg diet Improved body weight gain, feed efficiency in Japanese quails. [67] Fruit granules 200 g/kg concentrate mix Improved feed efficiency and egg production in Japanese quails.…”
Section: Morinda Product Inclusion Level Major Findings Sourcesmentioning
confidence: 99%
“…In another study, Morinda fruit extract supplementation at 1.5 ml/ bird/day improved weight gain, feed conversion ratio and dressing percentage in broilers compared to the control diet[66]. Sunder et al[67] also observed improved growth and feed utilisation of…”
mentioning
confidence: 99%